Improving the assessment of the non-life insurance market development level in Ukraine - Opeshko, Nataliya; Hontar, Daria; Kovalchuk, Viktoriia (Technology audit and production reserves, 2017)
Nowadays the non-life insurance market in Ukraine is on the stage of development. Therefore, it is necessary to assess the level of development of the non-life insurance market in Ukraine and to propose recommendations for improvement the activity of the non-life insurance companies. The article deals with the peculiarities of the insurer companies in Ukraine that carry out insurance other, than life-insurance. It was analyzed the national non-life insurance market during 2005-2015 that helped to determine the main problems of its development. For assessment of the non-life insurance market development level there were selected the indexes of amount of insurance companies, the amount of the insurance contracts and the volume of responsibility after them, the middle amount covered on one contract of insurance, the volume of gross and clean insurance bonuses, the level of diversification of insurance brief-cases of insurers, the strength of the insurance market, profitability of insurance and investment activity of insurance companies. Using correlation analysis it was eliminated the multicollinearity between selected parameters. It was calculated the integral indicator of the non-life insurance market development level in Ukraine using the method of taxonomy. On the basis of the scale authors conclude that during the analyzed period (2008-2015) the integral indicator of the insurance market development was not high. Only in 2010 and 2012 the insurance market development in Ukraine has reached average level. At all other times the activity of the insurance market was low.